Minor Physical Anomalies in Bipolar Disorder—A Meta-Analysis - Varga, Eszter; Hajnal, András; Soós, Alexandra; Hegyi, Péter; Kovács, Dóra; Farkas, Nelli; Szebényi, Júlia; Mikó, Alexandra; Tényi, Tamás; Herold, Róbert (Frontiers in Psychiatry, 2021)
Introduction: Minor physical anomalies (MPAs) may reflect basic neurobiological features underlying bipolar disorders (BPD), as they are sensitive physical indicators of morphogenetic failure of the brain. Despite several researches about the presence of MPAs in BPD, the results are still controversial. Objectives: The aim of the present meta-analysis was to assess the standardized weighted mean effect sizes of MPAs in BPD and to examine if MPAs may be found predominantly in the head and/or facial regions in BPD patients compared to controls (HC). Methods: Four studies, involving 155 patients with BPD, and 187 HC, were involved in the analysis after searching the literature. For the investigation of MPAs in the peripheral (MPA-P) and in the head and facial regions (MPA-CF), two studies involving 121 BPD patients, and 133 HC passed the inclusion criteria. Results: The number of the MPAs in the BPD group was significantly higher compared to HC. Another important finding of the present study is that BPD patients' MPA-P scores do not significantly differ from those of the HC. In contrast, BPD patients' MPA-CF scores were found to be significantly higher compared to HC subjects. It is important to note that there was a low number of eligible publications included, which caused higher heterogeneity. Conclusions: Low quality of evidence suggests that MPAs are more common in patients with BPD than in HC and the higher rate of MPAs is found predominantly in the head and facial regions.